Impact of a single, short morning bright light exposure on tryptophan pathways and visuo- and sensorimotor performance: a crossover study - Schobersberger, W.; Blank, C.; Hanser, F.; Griesmacher, A.; Canazei, M.; Leichtfried, V. (Journal of Physiological Anthropology, 2018)
Background: Bright light (BL) has been shown to be effective in enhancing both cognitive and physical performances. Alterations in nighttime melatonin levels have also been observed. However, evaluations of light-induced changes in the preceding biochemical processes are absent. Therefore, the impact of a single morning BL exposure on sensorimotor and visuomotor performance, as well as tryptophan (trp) and trp metabolites, was evaluated in this study. Methods: In a crossover design, 33 healthy volunteers were randomly exposed to 30 min of < 150 lx at eye level (office light, OL) and 5000 lx at eye level (bright light, BL) of 6500 K in the morning hours. Trp, sulfatoxymelatonin (aMT6s), and kynurenine (kyn) courses over the morning hours were analyzed, and changes in sensori- and visuomotor measures were examined. Results: Motoric performance increased in both setups, independent of light intensity. aMT6s and kyn decreased equally under both lighting conditions. Trp levels decreased from a mean (95% confidence interval) of 82.0 (77.2-86.9) to 66.5 (62.5-70.1) in the OL setup only. Conclusion: These data suggest that BL in the morning hours has a limited effect on visuo- and sensorimotor performance. Nevertheless, trp degradation pathways in the morning show diverse courses after OL and BL exposure. This suggests that trp courses can potentially be altered by BL exposure.